The Effectiveness of Using Community Language Learning Method Toward Students Speaking Ability - Iqbal (Juliet, 2021)
The purpose of this study was to determine whether the Community Language Learning Method (CLLM) is more effective on the ability to speak 11th-grade students of MIPA SMA Negeri 4, Tanjungpinang. This type of research used in this study is Quasi Research. The tool used to obtain research data is an oral test. The population in this study was eleventh grade students of SMA Negeri 4 Tanjungpinang. This study uses a method that requires students to carry out speaking activities in a group with topics that have been mutually agreed upon in each group. Researcher gave a pretest before learning activities. After the learning activities, the researcher gives a posttest that is added to the rubric of assessment, calculating the average value, and analyzing with the help of a computer application namely SPSS. The application of the Community Language Learning Method (CLLM) during the learning process turns out to have an effect on the ability of students to carry out conversations in groups that have been formed. It can be seen during the teaching and learning process students look more active and enthusiastic about learning to speak situations using the Community Language Learning Method (CLLM).